Sosialisasi Penggunaan Aplikasi Canva untuk Menunjang Kreativitas dalam Literasi Informasi Tenaga Perpustakaan UIN Gusdur Pekalongan - Arditya Prayogi; Ridho Aji Anggana; Ida Royani; Muhammad Nasrullah (Al-Nizam: Indonesian Journal of Research and Community Service, 2023)
The Canva application is an application that is capable of designing images in the form of posters, presentations, greeting cards, brochures, videos and so on which are done online, making it very easy for users to design. The use of this application is currently relevant to be able to present information or news that is interesting, creative and informative so that information can be produced that is easily accepted by readers, which in this case are users. This service activity aims to foster a sense of creativity in creating information media to support the digital information literacy of UIN Gusdur Pekalongan library staff. The method used is socialization supported by direct practical efforts. From the results of the activity, it is clear that this activity can increase the insight and knowledge of library staff in supporting creativity in creating information to support digital information literacy.